2008
DOI: 10.1590/s1516-89132008000100022
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of genetic diversity among the maize inbred lines (Zea mays L.) obtained by RAPD and SSR markers

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 28 publications
6
24
0
Order By: Relevance
“…RAPD have been used for different number of species, independent of the strategy of reproduction, with success as in Coffea arabica autogamous (Diniz et al 2005); C. canephora allogamous (Ferrão et al 2009), Aspidosperma allogamous (Torezan et al 2005), Zea mays self-fertilized (Souza et al 2008), Catharantus roseus (Shaw et al 2009), Cassava allogamous (Ferreira et al 2008). Chiari et al (2007) highlighted the importance of knowing the genetic variability in the Brachiaria germplasm bank accesses for successful plant breeding plans, planning of divergent crosses and guidance of new collections or germplasm exchange.…”
Section: Ac Ambiel Et Almentioning
confidence: 99%
“…RAPD have been used for different number of species, independent of the strategy of reproduction, with success as in Coffea arabica autogamous (Diniz et al 2005); C. canephora allogamous (Ferrão et al 2009), Aspidosperma allogamous (Torezan et al 2005), Zea mays self-fertilized (Souza et al 2008), Catharantus roseus (Shaw et al 2009), Cassava allogamous (Ferreira et al 2008). Chiari et al (2007) highlighted the importance of knowing the genetic variability in the Brachiaria germplasm bank accesses for successful plant breeding plans, planning of divergent crosses and guidance of new collections or germplasm exchange.…”
Section: Ac Ambiel Et Almentioning
confidence: 99%
“…Regarding RAPD markers, Rinaldi et al (2007) also did not infer a significant correlation between heterosis and productivity in Brazilian popcorn populations. Different studies have reported on the successful use of molecular markers in the evaluation of the genetic diversity in maize and its association with heterosis (Lanza et al, 1997;Sun et al, 2004;Souza et al, 2008). However, these studies did not use traits related to productivity.…”
Section: Resultsmentioning
confidence: 99%
“…Many factors could influence genetic distance values, such as the number of markers used and distribution of the markers in the genome (Munsch, 2008). In total, 21 markers were used in the study, and according to Souza et al (2008) 16 markers are enough for genotype analysis. Munsch (2008) analyzed 30 genotypes using 20 SSR markers and revealed 71 alleles, which is much less than the number of alleles obtained in this research.…”
Section: Plus-hybrid Effect On Grain Yieldmentioning
confidence: 99%